Dissipation of chlorpyrifos in a Malaysian agricultural soil: a comparison between a field experiment and simulation by the VARLEACH and PERSIST models - Ismail B.S.,; Halimah M.,; Tan, Y.A.; Tayeb M.A., (Penerbit Universiti Kebangsaan Malaysia, 2017)
A comparison of the dissipation of chlorpyrifos in a Malaysian agricultural soil was undertaken using data from a field experiment and simulation by the PERSIST model. The study was carried out at an oil palm estate located close to the Kuala Lumpur International Airport (KLIA), Sepang, Selangor (for field experiment). The plots were treated with chlorpyrifos at the manufacturer’s recommended dosage. Soil samples were collected according to the sampling schedule at intervals of 0, 1, 3, 7, 14, 21, 30, 60 and 90 days. Residues of chlorpyrifos in soil from the field trial were analyzed in the laboratory. Simulation of chlorpyrifos leaching and persistency was done using two computer-run software VARLEACH and PERSIST. Generally, predicted data for chlorpyrifos residue obtained using the VARLEACH and PERSIST models was found to be well matched with the observed data from the field trial. The PERSIST Prediction for chlorpyrifos residue in soils planted with oil palm trees was found to be accurate and conformed to the results observed in the field trial.